SINKRONISASI TATA RUANG WILAYAH KOTA BOGOR DALAM MENDUKUNG PROGRAM PEMBANGUNAN - Sigit Prayitno; Setia Hadi; Manuwoto Manuwoto (Diponegoro University, 2016)
The RTRW was intended to help The City Government to prepare an urban development guideline that includes the sectoral and spatial aspect. The synchronization between the development program with RTRW was conducted through application of spatial plan in the development program. The purpose of this study were: (1) analysis of the suitability of land use with RTRW; (2) analysis of the suitability of the development program with RTRW; (3) analysis of the spatial planning use in the preparation of the development program and its influencing factors; and (4) strategy formulations to improve the synchronization. The analytical method used in this study were: overlay analysis, descriptive analysis, and A'WOT. The results showed that the suitability of land use in 2013 with the spatial pattern plan is 59.58%, unrealized 36.41%, not suitable 4.01%. Average physical program in accordance with RTRW is 87.68%. 75% of agencies are already using RTRW in the preparation of the development program, while 25% of institutions did not. The prioritized strategy is to implement the regulations on spatial planning and development plan explicitly so that the city government's commitment can be realized.